Access to transport for women with hypovolemic shock differs according to weeks of pregnancy☆. Issue 2 (27th June 2014) - Butrick, Elizabeth; Penn, Amy; Itakura, Kaoru; Mkumba, Gricelia; Winter, Kelly; Amafumba, Rhoda; Miller, Suellen
Abstract: Objective: To examine whether women with hypovolemic shock secondary to obstetric hemorrhage are transported to referral hospitals differently depending on weeks of pregnancy in Zambia. Methods: In a retrospective study, transport type, wait time, and transit time were assessed for women with obstetric hemorrhage and hypovolemic shock transported from 26 primary health centers to three referral hospitals during 2007–2012. A mean arterial pressure of less than 60 mm Hg was used to indicate severe shock. Women were split into two categories on the basis of the number of weeks of pregnancy (< 24 weeks vs ≥ 24 weeks). Results: Overall, 616 women were included. Mode of transport differed significantly by group ( P < 0.001). 414 (93.0%) of 445 women at 24 weeks of pregnancy or more were transported by ambulance versus 114 (66.7%) of 171 women at less than 24 weeks. Among those in severe shock, 106 (93.0%) of 114 women at 24 weeks of pregnancy or more were transported in ambulances versus 26 (52.0%) of 50 women at less than 24 weeks ( P < 0.001). Conclusion: Women at 24 weeks of pregnancy or more were given preference for ambulance transport even when signs of shock were equivalent. Policy‐makers aiming to lower maternal mortality need to address transport issues regardless of the etiology of hemorrhage or week of pregnancy.